Examination of Orphaned Learners’ Perspectives on the Influence of Appreciative Project Design Orientation on Their Educational Achievements: The Case of Orphan Support Projects in Homa Bay County, Kenya - Odhiambo, Abuya Isaac; Rambo, Prof. Charles M. (International Journal of Scientific Research and Management (IJSRM), 2018)
It is estimated that 2.5 million of orphaned children live in Kenya, with Homa Bay County having the highest number of orphans, due to high incidences of adult AIDS related mortality. Available research suggests that orphaned learners have poor educational outcomes compared to non orphaned learners. To show commitments and support to the education of orphaned learners, the government of Kenya signed and supported the Declaration of the Right of the Child to Education, and has prioritized the education of orphaned learners, by investing financial and technical support towards the design and implementation of orphan support projects. It has been argued that the success of orphan support projects in promoting the education of orphaned learners depends on the extent to which these projects appreciate orphaned learners. However, despite the available evidence that projects that appreciate lead to improved educational outcomes learners, little research has examined the extent to which appreciative project design orientation  influence orphaned learners’ educational achievements. The objective of the study was to examine the influence of appreciative project design orientation on orphaned learners’ educational achievements in Homa County. The cross-sectional study was grounded on pragmatism. A total of 363 primary school orphaned learners in class 4-8 participated in the study. Orphaned learners’ survey questionnaire was used to collect data. To ensure validity and reliability of the research instruments, pilot testing was conducted in a community based orphan support project in the neigbouring Kisumu County. Cronbach alpha at α =0.05 level of significance was used to compute the reliability coefficient of the pre-test instruments. Inferentially simple and multiple linear regression , and Pearson Correlation Coefficient models were used to determine the extent to which appreciative project design orientations influenced orphaned learners’ educational achievements. Tests of statistical assumptions were carried out before data analysis to avoid invalidation of statistical analysis. One hypothesis was tested at α=.05 level of significance. H01: Appreciative design orientation does not significantly influence orphaned learners’ educational achievements in Homa Bay County was rejected since (F(10,353)=5.265; P=0.000